INCLUDING A JANE ACCELERATOR WORKING CAMERA (British Journal of Global Ecology and Sustainable Development, 2023)
In order to ensure the quality of cotton fiber, the article presents the effect of a working chamber with a ginning accelerator on the technological processes of ginning.